Políticas de control de cartera vencida y su incidencia en la gestión presupuestaria en el GAD Bolívar, periodo 2019-2022 - Cevallos Morales, Wilson Francisco (2025)
This research was conducted within the framework of overdue portfolio control policies and their impact on budget management at the Decentralized Autonomous Municipal Government in Bolívar Canton during the period 2019-2022. To address this issue, an exhaustive investigation was carried out through data collection. The general objective of the study was to analyze the overdue portfolio control policies and their impact on budget management at the GAD of Bolívar during the specified period. Legal foundations were included to provide a deeper understanding of the topic. The methodology applied involved the use of inductive-deductive methods, surveys, and interviews. Once the relevant analysis was completed, an improvement plan was proposed. After applying the research instruments, the obtained results allowed for the formulation of conclusions and recommendations. Finally, a preventive solution proposal was developed. Given that the portfolio recovery process remains one of the most pressing issues for GADs, this research aims to prevent further complications related to this problem.